Dual Agency in Hospitals: What Strategies Do Managers and Physicians Apply to Reconcile Dilemmas Between Clinical and Economic Considerations? - Waitzberg, Ruth; Gottlieb, Nora; Quentin, Wilm; Busse, Reinhard; Greenberg, Dan (International journal of health policy and management, 2022)
Hospital professionals are "dual agents" who may face dilemmas between their commitment to patients' clinical needs and hospitals' financial sustainability. This study examines whether and how hospital professionals balance or reconcile clinical and economic considerations in their decision-making in two countries with activity-based payment systems. We conducted 46 semi-structured interviews with hospital managers, chief physicians and practicing physicians in five German and five Israeli hospitals in 2018/2019. We used thematic analysis to identify common topics and patterns of meaning. Hospital professionals report many situations in which activity-based payment incentivizes proper treatment, and clinical and economic considerations are aligned. This is the case when efficiency can be improved, eg, by curbing unnecessary expenditures or specializing in certain procedures. When considerations are misaligned, hospital professionals have developed a range of strategies that may contribute to balancing competing considerations. These include 'reshaping management,' such as better planning of the entire course of treatment and improvement of the coding; and 'reframing decision-making,' which involves working with averages and developing tool-kits for decision-making. Misalignment of economic and clinical considerations does not necessarily have negative implications, if professionals manage to balance and reconcile them. Context is important in determining if considerations can be reconciled or not. Reconciling strategies are fragile and can be easily disrupted depending on context. Creating tool-kits for better decision-making, planning the treatment course in advance, working with averages, and having interdisciplinary teams to think together about ways to improve efficiency can help mitigate dilemmas of hospital professionals.